Biocombustíveis e economia de baixo carbono no Brasil - José Alex do Nascimento Bento; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study describes the relationship between GHG emissions and a set of economics and environmental variables in the energy sector of the 27 Brazilian states, during the period 2010 to 2020. The system Generalized Moments Method (system GMM) was used to verify the influence, in particular, of renewable energy, production and productivity of biofuels, population, GDP per capita and fleet of light cars on the emission of polluting gases. The results indicated that production of biofuels and the fleet of light vehicles tend to decrease CO2 emissions, while, population and GDP per capita had an increasing influence. It is worth noting that the variables - renewable energy and biofuel productivity - showed statistically non-significant effects.
Keywords: Q1; Q41; Q42; Q43; Q48; 330; renewable energy; CO2 emissions; biofuels; bioenergy; productivity